Islam in Armenian literary culture - Parsumean-Tatoyean, Seda (My University, 2021)
The Armenians' perspectives on and perceptions of Islam are some of the earliest and integral parts of Near Eastern interactive history, yet the subject remains in virtual obscurity. A novel and extensive study, 'Islam in Armenian Literary Culture. Texts, Context, Dynamics' is a maiden voyage into this unchartered territory and an overdue task in regional, Armenian and Interfaith studies. For greater clarity and ease of navigation, the book is organized around three main themes: the 'Armenian Mahmet', the 'Armenian Ghurans', and the 'Armenian Pax Islamica', from the seventh to the twenty-first centuries
Тexts, contexts, dynamics
Lovanii : In Aedibus Peeters, 2021. - xxxii, 384 pages ; 24 cm. - Includes bibliographical references and indexes
Գիրքը ՀԱԳ- ում բացակայում է։ Տվյալները՝ ինտերնետային կայքից
https://ebin.pub/islam-in-armenian-literary-culture-texts-contexts-dynamics-corpus-scriptorum-christianorum-orientalium-subsidia-tomus-147-699-9789042945029-9789042945036-9042945028.html
Keywords: Armenian literature-Islamic influences; History and criticism; Islam in literature